Occurrence, distribution, and ecological risk of bisphenol analogues in marine ecosystem of urbanized coast and estuary - Zainuddin, Azim Haziq; Roslan, Muhammad Qusyairi Jori; Razak, Muhammad Raznisyafiq; Md. Yusoff, Fatimah; Mohamad Haron, Didi Erwandi; Aris, Ahmad Zaharin (Elsevier, 2023)
Bisphenol analogues are prevalent globally because of rampant usage and imprecise processing techniques, prompting alerts about environmental and health hazards. The method employed in this study by solid phase extraction (SPE) and liquid chromatography-tandem quadrupole mass spectrometer (LC-MS/MS) for both quantification and qualitative analysis of the bisphenol compounds in the surface water samples. The coastal and estuarine surface water of Port Dickson and Lukut ranges from 1.32 ng/L to 1890.51 ng/L of bisphenol analogues. BPF mean concentration at 1143.88 ng/L is the highest, followed by BPA and BPS at 59.01 ng/L and 10.96 ng/L, respectively. Based on RQm for bisphenol analogues, the highest for BPF at 2.49 (RQ > 1, high risk), followed by BPS at 0.12 (0.1 < RQ < 1, medium risk) and BPA at 0.09 (0.1 < RQ < 1, medium risk). The presence and current risk of bisphenols analogues should alert the possible water quality degradation soon.